MAKANAN TRADISONAL TRITES DALAM TRADISI ERDEMU BAYU PADA MASYARAKAT KARO DI DESA SUKANALU - Muhammad Fauzi Alfachrezzy,; Muhammad Elfath Devgan,; Lila Pelita Hati,; Peninna Simanjuntak, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Trites is a typical Karo food made from grass in the stomach of a cow or buffalo that has not been processed or digested completely. Talking about ethnicity cannot be tied to all its multiculturalism, including one that includes food that is part of the local culture. Especially in traditional traditions or celebrations, weddings in the Karo tribe are often served with food which is also a local culture that is inherent in it, such as Trites, Kidu-kidu, and Cimpa. This study aims to get to know Trites in the erdemu bayu tradition. The Karo tribe itself is our priority for research because this tribe has traditional knowledge about food technology which is very unique and almost not found in other tribes in North Sumatra. This research and writing discusses the history of traditional food traditions in Tanah Karo and this research also aims to determine the context of food use in traditional festivals in Tanah Karo. The research method used is history, namely heuristics, criticism, interpretation and historiography. The results of the study show that this trites traditional food has its own uniqueness starting from the process of making it and its taste regarding how the trites are processed and the form of serving the trites from oral interviews with informants